The Climate change atlas for Africa of tree species prioritized for forest landscape restoration in Ethiopia: A description of methods used to develop the atlas - Kindt, R.; Abiyu, A.; Borchardt, P.; Dawson, Ian K.; Demissew, S.; Graudal, L.; Jamnadass, R.; Lillesø, J.-P.B.; Moestrup, S.; Pedercini, F.; Wieringa, J.J.; Wubalem, T. (CIFOR-ICRAF, 2023)
This working paper describes the methods used to develop the online Climate change atlas for Africa of tree species prioritized for forest landscape restoration in Ethiopia. The purpose of the atlas, available at http://atlas.worldagroforestry.org/, is to indicate how climate change is likely to affect the locations where particular tree species can grow in Africa. The atlas shows the baseline and 2050s habitat distributions across Africa for 127 tree species. Methods behind the creation of the atlas described in this working paper include: the selection of tree species; the processing and selection of predictor variables; the selection of future climates; the compilation of occurrence observations, and their spatial and environmental thinning; the compilation of background observations; the spatial folding of occurrence and background observations; the calibration of species distribution models and the generation of suitability maps; the discrimination of areas with novel environmental conditions; the generation of habitat change maps; and the creation of convex hulls for an a posteriori distance constraining method. This working paper is not a beginner’s guide to species distribution modelling; however, for users who also require an initial introduction, we provide references to appropriate resources.